Self-employment as a form of Economic Activity Conducive to Reducing Unemployment Among Young People in Poland - Buchelt, Beata Irma; Pauli, Urban; Pocztowski, Aleksy (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Unemployment among young people is one of the most important challenges of the European labor market. It is also a strategic issue of the Polish labor market. The strategic importance of this problem causes an increased interest not only on European Union level, but also on the country one. Researchers tend to identify reasons for this state of affairs, and attempts to mitigate this phenomenon. This article is part of a movement seeking solutions to the youth unemployment problem. The purpose of it is to describe the essence of self-employment, and the indication of the advantages of this form of economic activity on the labor market especially in the context of activation of young people. The article is divided into the following sections. First, it shows the status quo of youth unemployment in Poland. Subsequently, we discuss the essence of self-employment and bring closer to its’ characteristics. In the last part of the article we indicated the advantages and disadvantages of self-employment as an alternative economic activity of young people.